Pediatric Lung isolation in a limited resource setup: a case report - Baral, Pankaj; Prasad, Jagat Narayan; Bhandari, Sabin; Thapa, Pratistha (Journal of Society of Anesthesiologists of Nepal, 2019)
Rationale: Pediatric lung isolation is a great challenge to an anesthesiologist. Despite various advances in techniques and equipment in lung isolation, most of the sophisticated devices are unavailable in remote setups. Blind techniques have been used, but they have a low success rate. Patient concerns: Here we report a case of a five year old male child who had cough and fever for one month. CT scan of chest revealed right sided empyema thoracis for which decortication was planned under general anaesthesia with one lung ventilation. Double lumen tube for this patient was not commercially available and we did not have a paediatric fiberoptic bronchoscope, which would fit inside the endotracheal tube necessary for the patient. Interventions: After anesthesia induction, an adult fiberoptic bronchoscope was used as an aid for insertion of bougie into the left mainstem bronchus followed by rail roading the endotracheal tube over the bougie for lung isolation. Outcomes: Surgery then proceeded in left lateral position with a right thoracotomy under a quiet surgical field. Conclusion: In case of unavailability of paediatric fiberoptic bronchoscope, an adult fiberoptic bronchoscope and a bougie can aid in successful lung isolation in paediatric patients.